Penyelesaian Sengketa Tanah Overlapping Melalui Mediasi di Kantor Pertanahan Kota Semarang: (Studi Kasus Kelurahan Kalipancur, Kecamatan Ngaliyan, Kota Semarang) - Utari Zuhra Siregar (CV Rewang Rencang, 2025)
Overlapping land disputes are an agrarian issue that often arises in Indonesia, including in the city of Semarang. This study highlights the resolution of disputes over a plot of land in Kalipancur village, Ngaliyan district, which involves two different land ownership certificates for the same object. The purpose of this research is to examine the mediation process and the legal consequences of the agreement reached. The method used is a qualitative approach through case studies. The land office plays a crucial role in facilitating communication, assisting the resolution process, and ensuring that the mediation results have legal force and can be implemented by both parties.